Penerapan Metode Multiple Discriminant Analysis untuk Mengukur Tingkat Kesehatan yang Mengindikasikan Gejala Financial Distress pada Bank Umum Syariah - Nada, Shofaun (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
This research aims to account, analyse and compare the level ofIslamic commercial bank’s health using CAMELS method mentioned in PBI No.9/1/PBI/2007 and SEBI No 9/24/DPbS/2007 and using multiple discriminant analysis (MDA) altman z-score method. There are only four of six factors that used in CAMELS: capital, asset, earning and liquidity excluding Management and Sensitivity of Market Risk factor. The variables of capital factors are KPMM and ECR ratio. Asset factor consist of KAP and NPF ratio. Earning factor contains four ratios, such as NOM, ROA, ROE and REODOI: 10.15408/aiq.v5i2.2566